Tingkat Kesejahteraan Psikologis Siswa SMPN 1 V Koto Timur Selama Masa Pandemi Covid-19 - Monalisa Monalisa (Jurnal Halaqah, 2021)
The purpose of study is to see how the level of psychological well-being of students at SMP N 1 V Koto Timur during the Covid-19. The method used is a quantitative approach with a descriptive survey method. The population was all students of SMP N 1 V Koto Timur. The research subjects consisted of 125 students. The sampling technique is simple random sampling. The results showed that students who were at the level of psychological well-being in the high category were 60.8%, the moderate category was 39.2%, and the low category was 0%. So it can be concluded that the level of psychological well-being of SMP N 1 V Koto Timur students during the covid-19 pandemic is in the high category.